Reading in the Scroll Era: Generation Z's Digital Literacy in a Culture of Quick Forgetfulness - Ruslan, Mamat; Barkah; Thakur, Ibtasam; Lyesmaya, Dyah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores how Generation Z navigates reading practices in the digital era, particularly within the context of infinite scroll architecture and the attention economy. Using a qualitative phenomenological approach, data were collected through in-depth interviews, focus group discussions, non-participatory observation, and content analysis involving 28 university students aged 18–23. Thematic analysis revealed five key findings: (1) information overload and the illusion of novelty lead to a preference for speed over depth; (2) skimming serves as an efficient survival strategy but results in superficial understanding; (3) despite the dominance of fast content, participants still long for deep reading experiences; (4) visual cues, such as emojis and memes, influence engagement and credibility judgments; (5) hybrid literacy strategies emerge as a way to balance quick consumption with in-depth analysis. The study highlights the adaptive strategies that Generation Z uses to manage the tension between fast, fragmented content and the desire for sustained engagement. The implications of these findings suggest that educators should promote hybrid literacy approaches in the curriculum, encouraging students to combine fast and slow reading practices. For platform designers, incorporating features that facilitate both quick access to information and opportunities for deeper engagement could improve the quality of digital reading experiences.